Clinical and molecular profiling of AML patients with chromosome 7 or 7q deletions in the context of TP53 alterations and venetoclax treatment. Issue 13 (10th November 2022) - Abbas, Hussein A.; Ayoub, Edward; Sun, Hanxiao; Kanagal-Shamanna, Rashmi; Short, Nicholas J.; Issa, Ghayas; Yilmaz, Musa; Pierce, Sherry; Rivera, Daniel; Cham, Brent; Wing, Shane; Li, Ziyi; et al.
Abstract: Deletions in chromosome 7 (del(7)) or its long arm (del(7q)) constitute the most common adverse cytogenetic events in acute myeloid leukemia (AML). We retrospectively analyzed 243 treatment-naive patients with AML and del(7) (168/243; 69%) or del(7q) (75/243; 31%) who did not receive any myeloid-directed therapy prior to AML diagnosis. This is the largest comprehensive clinical and molecular analysis of AML patients with del(7) and del(7q). Our results show that relapse-free survival was significantly longer for AML patients with del(7q) compared to del(7), but the overall survival and remission duration were similar. TP53 mutations and del5/5q were the most frequent co-occurring mutations and cytogenetic abnormalities, and conferred worse outcomes in del(7) and del(7q) patients. Venetoclax-based treatments were associated with worse outcomes in TP53 mutated AML patients with del(7) or del(7q), as well as del(7) with TP53 wildtype status, requiring further investigation.